2015
DOI: 10.1093/eurpub/ckv172.006
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine dependence and urinary nicotine, cotinine and hydroxycotinine levels in daily smokers

Abstract: Introduction: Nicotine dependence and smoking frequency are critical factors for smoking cessation. The aims of this study are 1) to determine if nicotine dependence FTND scores are associated with urinary levels of nicotine metabolites, 2) to assess the relationship of hydroxycotinine/cotinine ratio with FTND score and cigarettes smoked per day (CPD) and 3) to identify significant predictors of cigarettes per day among biomarker concentrations and individual FTND items. Methods: Urine samples and questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Some previous studies have shown a significant positive correlation between the concentration of urinary cotinine and the levels of nicotine dependence and CPD, both of which are predictors of quitting behavior (DiFranza et al, 2013;Jung et al, 2012;Van Overmeire et al, 2016). However, these studies did not assess the correlation in heavy smokers with severe nicotine dependence.…”
Section: Discussionmentioning
confidence: 94%
“…Some previous studies have shown a significant positive correlation between the concentration of urinary cotinine and the levels of nicotine dependence and CPD, both of which are predictors of quitting behavior (DiFranza et al, 2013;Jung et al, 2012;Van Overmeire et al, 2016). However, these studies did not assess the correlation in heavy smokers with severe nicotine dependence.…”
Section: Discussionmentioning
confidence: 94%
“…A cross-sectional study of 239 smokers measuring urinary nicotine, cotinine, and 3-HC found that levels of all three of these markers were positively correlated with FTND scores (29). The time to first cigarette (TTFC) item of the FTND was positively correlated with urinary levels of nicotine, cotinine, and 3-HC.…”
Section: Resultsmentioning
confidence: 99%
“…Expired CO is increased acutely (6-9 hours) after combustible tobacco use, whereas cotinine, the primary metabolite of nicotine, has a longer half life (5-7 days) thus giving a longer-term measure of exposure to nicotine, regardless of the route of administration (21). However, growing evidence suggests that these, other exposure markers, are associated with dependence severity and risk of relapse (22, 23). Biomarkers not directly related to nicotine metabolism have been increasingly studied in TUD, such as markers of cardiovascular disease (CVD), inflammation, oxidative stress, and hypothalamic-pituitary-adrenal (HPA) axis reactivity (24-26).…”
Section: Introductionmentioning
confidence: 99%